Analysis of English Learning Strategies Performed by Successful EFL Learners in Non-English Department - Saputri, Rizky Ambar; Lalu Thohir; Ahmad Junaidi (Journal of English Education Forum (JEEF), 2024)
The objectives of this research were to know and describe English learning strategies that are used by successful EFL learners in non-English departments at the University of Mataram and the factors driving them. This is a descriptive qualitative study using purposive sampling. The samples were 5 Engineering students and 5 Economics students with TOEFL scores of 457 to 560. The data was collected through the Strategy Inventory for Language Learning (SILL) questionnaire version 7.0 and semi-interview. The result of the study reveals that successful EFL learners in Engineering and Economics implement all learning strategies at two different levels. The learners use compensation, metacognitive, and cognitive strategies at a high level, then memory, social, and affective strategies at a medium level. This research found that each learning strategy that the learners performed is intertwined. The naturalistic factors that contribute to driving the appropriation and implementation of those strategies are their English proficiency, learning style, and motivation. While there is no significant influence from gender identity found in this research.